Perancangan Excellent Management System (EMS) pada Standarisasi Aset Kendaraan di PT SPIL - Richardo Caprianto; I Gede Agus Widyadana; Nova Sepadyati (Jurnal Titra, 2021)
PT Salam Pacific Indonesia Lines (SPIL) is a company engaged in shipping logistics and operates in 42 branches spread throughout Indonesia, With the increase in the size of the company, the number of vehicles used for automatic operations increases, The difficulty of transport maintenance and complicated administrative processes is enough to hinder PT SPIL to operate on field. Therefore, the researcher created a project to standardize the management process with an Excellent Management System (EMS). EMS is a standardized system according to the administrative needs of PT SPIL, EMS has 3 important features, namely transport document extension, transport service, and transport rotation which also applies important industry knowledge such as simple moving average, weighted moving average, exponential smoothing along with the error. This research will result in standardization for PT SPIL vehicle asset management in document extension, vehicle repair, and when you want to rotate the vehicle in the form of existing forms and reminders and there is a calculation to measure the number of kilometers each day on EMS. The results of this EMS will later be used for the YES department at PT. SPIL.